Penyuluhan Kesehatan Masyarakat Tentang Cemaran Udara Ambien dan Efek Kesehatan bagi Operator SPBU di Kota Ternate - Sidebang, Purnama; Sakriani, Sakriani (Jurnal Pengabdian UNDIKMA, 2025)
This community service aims to improve the competence of gas station operators in Ternate City in behaving healthily and safely while working by increasing knowledge about ambient air pollution and its health effects. The procedure for implementing this activity begins with a pretest, counseling, demonstration of the use of personal protective equipment (PPE), distribution of pocket books and leaflets and ends with a posttest. Data analysis is carried out descriptively and analytically. Descriptively to see the percentage of PPE use and analytically using the Wilcoxon test to see the difference in operator knowledge before and after counseling. The results show that there is an increase in gas station operators’ knowledge about air pollution and its health effects and there is a change in behavior in the use of PPE while working. This service activity provides positive benefits for gas station operators and managers, marked by the high enthusiasm of the participants in each series of activities and the willingness of gas station managers to carry out the sustainability of this activity in the future.